Hepatitis C virus antibodies in outpatients with chronic kidney disease - Skladany, Lubomir (Clin Exp Hepatol, 2018)
AIM OF THE STUDY: To determine the seroprevalence of hepatitis C virus (HCV) in outpatients with chronic kidney disease (CKD) attending a nephrology clinic. MATERIAL AND METHODS: Prospective observational study on consecutive outpatients attending a nephrology clinic. Inclusion criteria were age > 18 years, CKD, informed consent. There were no exclusion criterias. Recorded variables were age, gender, CKD grade and etiology, anti-HCV antibodies (Ab). Patients with positive HCV Abs were tracked for HCV RNA detection. Study interval was from November 2015 to March 2016. The study has been approved by the Ethic committee of F.D. Roosevelt University Hospital. Funded by Restricted Grant of AbbVie Slovakia. RESULTS: One hundred and thirty-four patients were enrolled, with median age 70 years (19.7-91), 52% women. CKD grades: G1/2 – 52 patients (39%), G3a – 34 patients (25%), G3b – 32 patients (24%), G4 – 8 patients (6%), G5 – 8 patients (6%); CKD etiology: tubulointerstitial nephritis (TIN) – 53 patients (40%), nephrosclerosis (NS) – 30 patients (22%), diabetic nephropathy (DN) – 23 patients (17%), glomerulonephritis (GN) – 23 patients (17%), others – 5 patients (4%). Anti-HCV antibodies were detected in 8 patients (6%). There were no significant differences in CKD grades between HCV+ and HCV– patients; Heymann nephritis and GN were significantly more frequent in HCV– patients, as was male gender. Of 8 HCV Ab positive patients, 5 were available for HCV RNA testing (2 died after completion of the study, 1 was lost to follow-up); of them, 1 patient tested positive. CONCLUSIONS: Prevalence of anti-HCV antibodies in CKD patients was 6%, which is 4 times higher than in the general population of Slovakia; HCV RNA was detected in 1 patient (12.5%) of anti-HCV positive patients. Based on this result, multicentric, a larger-scale study is considered to be warranted.